Brand Awareness and Trust as a Factor The Determinant of Customer Loyalty: The Role of Mediation Customer Satisfaction - Michelle, Audrey Twyla; Pramadanti, Rindika (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the effect of brand awareness and trust on customer satisfaction and customer loyalty at Chatime, both directly and indirectly through satisfaction as a mediating variable. The research seeks to understand how consumers’ perceptions of a popular beverage brand influence their satisfaction levels and long-term loyalty. Primary data were collected from 190 respondents using a five-point Likert-scale questionnaire distributed through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS version 3.0. Hypothesis testing was conducted by evaluating path coefficients, T-statistics, and P-values to determine the significance of relationships among variables. The results show that brand awareness has a positive and significant effect on customer satisfaction and customer loyalty. Trust also positively influences satisfaction and loyalty, although its direct effect on loyalty is not always significant. Furthermore, customer satisfaction acts as an important mediating variable that strengthens the relationship between brand awareness, trust, and loyalty. Satisfying customer experiences, including product quality, service performance, and price fairness, encourage repeat purchases and long-term commitment. Therefore, strengthening brand image, maintaining trust, and improving overall customer experience are essential strategies to enhance loyalty in the competitive beverage industry.